Waveform-based selection of acoustic emission events generated by damage in composite materials. (February 2015) - Maillet, Emmanuel; Morscher, Gregory N.
Abstract: Acoustic emission (AE) has been shown to be a promising health monitoring technique for composite materials as it allows real-time location and identification of damage. When attempting to relate the recorded acoustic emission to a material׳s mechanical behavior, the relevance of results relies on an accurate selection of AE originating from material damage. Indeed, during mechanical tests most of the recorded AE is generated outside of the volume of interest and without proper filtering these AE signals can significantly affect the analysis. To date, there exists no common procedure for the selection of AE signals and therefore results can hardly be compared or transposed to different composite systems. In the present paper, a new waveform-based procedure is proposed for the selection of AE events generated by damage. The procedure includes accurate localization and selection assessment based on signal energy. Highlights: The present method allows accurate selection of AE events generated by damage. It uses an AIC-based localization technique and a new energy-based approach. It is demonstrated using artificial sources and applied to two composite systems.